(untitled) (Tempo e Argumento, 2011)
The purpose of this study is to present the assessment of how the implementation of equity public policies impacted Spain since the restoring of democracy, especially at the local administrative sphere and through known equity plans. It is arguable if these advancements that supposedly granted women the right of full citizenship actually have been translated into concrete actions, or if the gender role and stereotype still prevail, rendering them invisible both as a group and as individuals. Remembering our origins always prevents forgetting where we stand and how many tears, effort and sacrifices were endured before we were heard and taken into account. This review addresses the work carried out in Spain.